Nonedible thevetia peruviana oil for the synthesis of biobased thermosets and vitrimers with tunable mechanical properties - Olosho, Adebayo Isaac; Alam, Md Shafi; Sukumaran Nair, Kiran; Ambade, Ashootosh V.; Adekola, Folahan Amoo (ACS Applied Polymer Materials, 2024)
Current attempts to replace fossil-derived materials with vegetable oils for polymer production mainly rely on edible oils. This approach raises sustainability concerns due to potential food security risks. This report introduces the first in-depth examination of Thevetia peruviana oil (TPO) epoxidation, an easily accessible nonedible vegetable oil, utilizing diverse acidic ion-exchange resins as catalysts. It is followed by the development of vitrimers based on epoxidized oil (ETPO) with various dicarboxylic acid hardeners. Amberlite IRC120H emerged as the most effective catalyst for the epoxidation of the oil, allowing for repeated catalyst reusability for up to five cycles. An impressive relative oxirane conversion of 98.9% was achieved after optimization. DSC analysis revealed that among the diacids, 2,2'-dithiodibenzoic acid (DTBZ) has the lowest activation energy with ETPO. Additionally, the ETPO-DTBZ-based thermosets displayed exceptional solvent resistance and thermal stability, indicative of a high degree of cross-linked networks within the system. Mechanical analyses revealed that all aliphatic hardeners resulted in soft materials, while DTBZ resulted in thermosets with tensile stress and modulus of 15 and 843 MPa, respectively. Consequently, DTBZ-ETPO thermosets were successfully recycled, repaired, and reshaped with minimal changes in the mechanical properties. The shape memory of the thermosets was also established.
Keywords: biobasedvitrimers; environmental sustainability; epoxidizedThevetial peruviana oil; nonedible oil; Optimization; shape memory

Synthesis and characterization of thermosetting adhesives from epoxidized Thevetia peruviana oil for sustainable bonding solutions - Kambikanam, Karthika Vayalachery; Bindu, Bhadra Purushothaman; Olosho, Adebayo Isaac; Nair, Kiran Sukumaran (RSC Sustainability, 2025)
<div class="abstract author" id="aep-abstract-id5" style="box-sizing: border-box; margin: 0px 0px 8px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> The demand for bio-based epoxy thermoset alternatives within the adhesive industry has seen substantial growth in recent years. This increase is attributed to a heightened exploration of renewable materials, including biopolymers and monomers derived from renewable resources. However, despite these significant advancements, a considerable portion of the research primarily focuses on edible oils, which may inadvertently neglect critical implications for food security. So, this study explores the thermal, mechanical, and adhesive properties of epoxy thermosets derived from biobased epoxidized Thevetia peruviana oil (ETPO) cured with two diamines, 1,10-decane diamine (DDA) and m-xylene diamine (XDA), using imidazole (IM) as a catalytic initiator. The thermosets were evaluated for lap shear strength on stainless steel (SS) and aluminium (Al) substrates at varying imidazole concentrations (0–5%) and curing times (24–96 hours). The results show that DDA-cured thermosets demonstrate superior thermal stability and heat resistance, with T5% increasing from 149 °C to 256 °C and THRI from 139 °C to 162 °C as IM concentration rises. XDA-cured thermosets exhibit higher adhesive strength, peaking at 1.47 MPa on SS at 5% IM and 72 hours, but lower thermal stability, with T5% values decreasing from 157 °C to 68 °C. Imidazole's catalytic efficiency enhanced the crosslinking in both systems, with DDA providing better thermal stability and XDA delivering higher adhesive strength. These findings demonstrate the potential of ETPO-based thermosets as sustainable adhesives, offering excellent performance for industrial applications. <div class="abstract graphical" id="aep-abstract-id7" style="box-sizing: border-box; margin: 0px 0px 8px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> The demand for bio-based epoxy thermoset alternatives within the adhesive industry has seen substantial growth in recent years.